PENGARUH MODEL PEMBELAJARAN COOPERATIVE LEARNING SCRIPT TERHADAP TINGKAT PEMAHAMAN SISWA PADA MATA PELAJARAN EKONOMI DI SMK BUSTANUL ULUM AS-SURUR - Shohifatul Maisyaroh; Pudhak Prasetiyorini; Febrina Gerhani (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to determine the differences in students' understanding using the cooperative learning script model with the conventional learning model at SMK Bustanul Ulum As-surur. This type of research is a quasi-experimental study with a nonequivalent control group design. The population in this study were all students of SMK Bustanul Ulum As-surur totaling 30 students. The sample of this study was 30 people divided into two classes, namely 15 students in the experimental class and 15 students in the control class. The sample was taken using a saturated sampling technique because the population was small. The subjects in this study were teachers and students, while the object was the effect of the cooperative learning script model on students' understanding of economics. Data collection used observation, tests, documentation. The data analysis technique for this study used the t-test (Independent Sample Test). The results of the study stated that the cooperative learning script learning model had a significant influence on the level of students' understanding of Economics at SMK Bustanul Ulum As-surur. Based on the independent sample t-test obtained at 0.001 with a significance of 0.001 <0.05, H0 is rejected and H1 is accepted, which means that there is a significant difference between the level of understanding of students who use the cooperative learning scipt learning model and the level of understanding of students who use the conventional learning model in the subject of Economics at SMK Bustanul Ulum As-surur.